Single institution study of the immune landscape for canine oral melanoma based on transcriptome analysis of the primary tumor - Vanhaezebrouck, Isabelle F.; Bakhle, Kimaya M.; Mendez-Valenzuela, Carlos R.; Lyle, L. Tiffany; Konradt, Kristoph; Scarpelli, Matthew L. (Frontiers in Veterinary Science, 2024)
Understanding a tumor’s immune context is paramount in the fight against cancer. Oral melanoma in dogs serves as an excellent translational model for human immunotherapy. However, additional study is necessary to comprehend the immune landscape of dog oral melanomas, including their similarity to human melanomas in this context. This retrospective study utilizes formalin-fixed paraffin-embedded (FFPE) tissue samples to analyze RNA sequences associated with oral melanoma in dogs. The focus is on understanding the differences between melanoma tumors restricted to the oral cavity (OL) and the same primary oral tumors with a history of metastasis to the lymph nodes or other organs (OM). Normal buccal mucosa samples are also included as a normal tissue reference. In the OM patient group, gene signatures exhibit significant changes relative to the OL patient group, including significantly decreased expression of S100, BRAF, CEACAM1, BCL2, ANXA1, and tumor suppressor genes (TP63). Relative to the OL tumors, the OM tumors had significantly increased expression of hypoxia-related genes (VEGFA expression), cell mobility genes (MCAM), and PTGS2 (COX2). Moreover, the analysis of the immune landscape in the OM group indicates a shift from a possible “hot” tumor suppressed by immune checkpoints (PDL1) to significantly heightened expression not only of those checkpoints but also the inclusion of other immune blockades such as PD1 and IDO2. In addition, the OM group had significantly reduced expression of Toll-like receptors (TLR4) and IL-18 relative to the OL group contributing to the tumor's immune escape. Additionally, signs of immune cell exhaustion are evident in both the OM and OL groups through significantly increased expression of TIGIT relative to normal tissue. Both the OM and OL groups had significantly increased expression of the immune cell marker CD4 relative to normal tissue. Further, CD4 expression was significantly decreased in OM relative to OL; however, the specific cell types expressing CD4 in OM and OL tumors cannot be determined from this study. A more in-depth investigation involving immunohistochemistry analysis and single-cell RNA expression is necessary to confirm these findings.